PERLINDUNGAN PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP IKLAN TELEVISI YANG BERMUATAN MATERI PORNOGRAFI MELALUI CLASS ACTION - Radhyca Nanda (Faculty of Law, Maranatha Christian University, 2019)
Advertising is a medium of communication directly with producers (business actors) to the audience / prospective consumers and consumers, of course here is expected by producers, one of which introduces products (both goods and services) to consumers and hopes consumers, through persuasion, are willing to consume them. Through advertisements, business actors refer to something related to their products to consumers. Because business people take various ways that are considered to be able to convey their messages effectively and efficiently. Business actors also choose media that are considered more appropriate for that. Reflecting on the educational background, social status, culture, ethnicity, religion, and others from the target consumers also influences the strategies of business people to advertise their products. Considering the loss caused by the broadcasting of advertisements has a massive impact and is felt by many consumers, which of course is not small, and has the same importance due to the losses suffered, consumers are more right to restore their rights to file a group representation as adopted in the Indonesian legal system Perma Nomor 1 Tahun 2002 Tentang Acara Gugatan Perwakilan Kelompok Keywords : Advertising; Businessmen; And Consumer.